Волынская вариантная модель хорового искусства в социокультурном континууме западного региона Украини периода Независимости - Марач, Олександр М.; Marach, Oleksandr M.; Марач, Александр Н. (Akademii Pomorskiej w Słupsku, 2015)
The concept of academic choral art in the social and cultural continuum of the Western region of Ukraine by Independence period for example by Volyn is justified in the research. The variations of definitions of „sociocultural continuum”, „author performing school”, „Ukrainian choir school” are filed, the chamber choir model, definitions of Apollonical and Dionysian archetypes in choral-conducting performance are justified. The trends of the choral art on the through by interviews with leading conductors of the western region and survey the thought of audience are investigated. This model is shows in the three aspects: the activity of groups (chamber choir „Oranta”, Chorus by Lutsk St. Peter and Paul church), methodological traditions, competitive-festival process. As an example of application of management in culture the version of organization of Choral art competition by Lesya Ukrayinka is submitted.
The Volyn choral art variant model in a socio-cultural continuum of western region of Ukraine by independence period
Keywords: Волынское академическое хоровое искусство; Volyn academic choral art; вариативная модель; variant model; социокультурный континуум; socio-cultural continuum; хоровая школа; choir school; исполнительская традиция; performing tradition; тенденция; trend; конкурсно-фестивальный процес; competitively-festival process; музыкальный менеджмент; music management